Analysis of raw material planning in company using the material requirement planning - peter setiawan; Indrianawati Usman (Institute of Computer Science (IOCS), 2023)
One of the problems that often occur in industrial companies is related to the inventory of raw materials. It is closely related to the production process, which can speed up or slow down. The researchers analyzed the existing business process model and Material Requirement Planning (MRP) model and the transformation of the two business process models. The processing of primary and secondary data was carried out with the MRP model approach and showed that the Lot for Lot method provides savings in ordering and purchasing raw materials. Besides, it provides savings in raw material inventory costs from January 2020-December 2021. The need for a Bill of Materials is also more controlled using the MRP system model.